Antenatal Corticosteroids and Postnatal Fluid Restriction Produce Differential Effects on AQP3 Expression, Water Handling, and Barrier Function in Perinatal Rat Epidermis - Johan Agren; Sergey Zelenin; Lill-Britt Svensson; Lene N. Nejsum; Soren Nielsen; Anita Aperia; Gunnar Sedin (Dermatology Research and Practice)
Loss of water through the immature skin can lead to hypothermia and dehydration in preterm infants. The water and glycerol channel aquaglyceroporin-3 (AQP3) is abundant in fetal epidermis and might influence epidermal water handling and transepidermal water flux around birth. To investigate the role of AQP3 in immature skin, we measured in vivo transepidermal water transport and AQP3 expression in rat pups exposed to clinically relevant fluid homeostasis perturbations. Preterm (E18) rat pups were studied after antenatal corticosteroid exposure (ANS), and neonatal (P1) rat pups after an 18 h fast. Transepidermal water loss (TEWL) and skin hydration were determined, AQP3 mRNA was quantified by RT-PCR, and in-situ hybridization and immunocytochemistry were applied to map AQP3 expression. ANS resulted in an improved skin barrier (lower TEWL and skin hydration), while AQP3 mRNA and protein increased. Fasting led to loss of barrier integrity along with an increase in skin hydration. These alterations were not paralleled by any changes in AQP3. To conclude, antenatal corticosteroids and early postnatal fluid restriction produce differential effects on skin barrier function and epidermal AQP3 expression in the rat. In perinatal rats, AQP3 does not directly determine net water transport through the skin.